MANAJEMEN EDUKASI PENGELOLAAN SAMPAH YANG BAIK DAN BENAR PADA SMK MUHAMMADIYAH 3 TERPADU PEKANBARU - Azmi, Fauzan; Irawan, Dika; Hidayat, Novit; Primadayani, Syurti; Nurhayati , Nurhayati (Komunitas Manajemen Kompetitif, 2024)
This service activity is based on basic questions regarding environmental management that can be carried out by middle school age children, especially female students at SMK Muhammadiyah 3 Pekanbaru, based on the boundaries of waste science which in English is called waste, which basically includes many definitions of waste, namely substances or objects that no longer used either in the form of waste materials originating from household waste or from factories as industrial waste, waste itself consists of two types, namely organic waste and inorganic waste, both types of waste according to law number 18 of 2008 concerning waste management, waste has become a problem national so that management is needed so that it does not cause negative impacts on public health and the environment The final result desired in this activity is how the students of SMK Muhammadiyah 3 Pekanbaru in particular can understand and understand how to manage waste properly and correctly and understand what the impact is if they do not protect the environment from an early age, and in the future it is hoped that efforts will be made if waste These are reused without undergoing a new process or transformation, for example a drink bottle turns back into a drink bottle